Major Bioactive Compounds of Pilis Plant Materials: A GC-MS Analysis - Timotius, Kris Herawan; Sari, Ita Novita; Santoso, Adit Widodo (Pharmacognosy Communications)
Background: As indigeneous herbal medicine (jamu) in Central Java, Indonesia, Pilis is applied topically to the forehead to cure dizziness, hazy vision, and eyestrain. For the future implementation, it is important to know the composition of plant materials used for Pilis and their major bioactive compounds. Aims of the study: This study aimed to determine the plant materials used for blending Pilis, and the major bioactive compounds of every plant materials. Materials and Methods: The blended plant materials for Pilis from homemade producers were collected and identified. For determination of bioactive compounds of every plant materials, extraction was done with hexane. The obtained crude extracts were analysed by GC-MS. Results: Eighteen plants materials of Pilis can be divided in two groups. The first group was the essential plant materials: Acorus calamus L., Alyxia stellata (J.R. Forst & G.Forst.) Roem & Schult., Curcuma heyneana Valeton & Zijp., Foeniculum vulgare Mill., Kaempferia galanga L., Melalueca leucadendra (L.) L., Rosmarinus officinalis L., Syzygium aromaticum (L.) Merr. & L.M. Perry, Zingiber montanum (J.Koenig) Link ex A.Dietr, Zingiber officinale Roscoe. The second group was the non-essential materials: Amomum compactum Sol. Ex Maton, Cinnamomum verum J.Fresl, Cryptocarya massoy (Oken) Kosterm, Curcuma longa L., Piper cubeba L.f., Pluchea indica (L.) Less., Trigonella foenum-graecum L., and Usnea filipendula. Several identified major bioactive compounds were amyrin, asarone, cinnamaldehyde, 1,8-cineole, dimethoxy phenyl butadiene (DMPBD), ethyl p-methoxycinnamate, eugenol, selinene, 4-terpineol, and zingerone. Conclusion: At least ten different plant materials are used for Pilis blending which has one or have limited number of dominant bioactive coumpounds.
Keywords: Bioactive compound; GC-MS; Jamu; Java; Pilis; Topical herbal medicine